Effect of 2,4-D on Indirect Somatic Embryogenesis and Surface Structural Changes in Garlic (Allium sativum L.) cv. Lumbu Hijau - Totik Sri Mariani; Hiroshi Miyake; Rizkita Rachmi Esyanti; Ida Nurwendah (Jurnal Matematika & Sains, 2003)
A study concerning the effect of 2,4-D on indirect somatic embryogenesis and surface structural changes in garlic (Allium sativum L.) cv. Lumbu Hijau was conducted. The purposes of this study were to evaluate the effect of 2,4-D on the induction of somatic embryogenesis and to observe the developmental stage of somatic embryo as well as the surface structural changes of somatic embryo in garlic. Root tips explants were cultured on embryogenic callus induction medium (ECIM). Somatic embryos were then transferred to the embryo maturation medium (EMM), desiccated and subsequently transferred to the repetitive somatic embryogenesis medium (RSEM). Observation by dissecting microscope showed that embryogenic callus and somatic embryo was formed at ECIM containing 0.1 Î¼M 2,4-D. At EMM containing 0.01 Î¼M 2,4-D somatic embryo developed into mature somatic embryo. Somatic embryo underwent repetitive somatic embryogenesis that consisted of globular and mature somatic embryo at RSEM, without plant growth regulator. Observation by scanning electron microscopy showed that the development al stages of garlic somatic embryo consisted of proembryo, transition phase from proembryo to globular, globular, mature embryo and single cotyledon stages. Effect of 2,4-D on the cell surface structure could be seen on each somatic embryo developmental stage. In ECIM containing 0,1 Î¼M 2,4-D, proembryo, transition embryo and globular embryo were formed. The surface of proembryo was smooth whereas fibrillar material as cellulose microfibril, was observed during the transition from proembryo to globular stage. The surface of globular stage was entirely covered by a new cell wall. Subsequently, in 0.01 Î¼M 2,4-D, mature embryo and single cotyledon were formed, which their cell wall surface was stable. From this study, it could be concluded that the optimum concentration of 2,4-D for induction of embryogenic callus and initiation of somatic embryo was 0.1 Î¼M. Decreasing of 2,4-D concentration to 0.01 Î¼M resulted in the development of globular embryo to mature and single cotyledon stage. Repetitive somatic embryogenesis occurred in RSEM medium without plant growth regulator. Based on this result it can be concluded that each somatic embryo developmental stage had a typical characteristic of surface structure.